2018
DOI: 10.1200/jgo.18.00093
|View full text |Cite
|
Sign up to set email alerts
|

Ablative Therapies for Cervical Intraepithelial Neoplasia in Low-Resource Settings: Findings and Key Questions

Abstract: Barriers to access for cervical precancer care in low-resource settings go beyond cost. Gas-based cryotherapy has emerged as the standard treatment in these areas, but there are barriers to this technology that have necessitated the development and implementation of affordable and portable alternatives. This review identifies knowledge gaps with regard to technologies primarily used in low-resource settings, including standard cryotherapy, nongas-based cryotherapy, and thermoablation. These gaps are addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…A good number of observational studies and only one RCT by Singh et al, (1988) have demonstrated the high efficacy of TA to treat histopathology proved cervical neoplasias in various settings and even in the HIV infected women (Hussein and Galloway, 1985;Smart et al, 1987;Gordon and Duncan, 1991;Joshi et al, 2013;Campbell et al, 2016;Naud et al, 2016). However, several meta-analysis and systematic reviews of such studies underscored the paucity of information related to the adverse events during and after the procedure (Dolman et al, 2014;Cremer et al, 2018;Randall et al, 2019). Concerns have been expressed by some authors regarding the possibility of the women feeling more pain during TA (Maza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A good number of observational studies and only one RCT by Singh et al, (1988) have demonstrated the high efficacy of TA to treat histopathology proved cervical neoplasias in various settings and even in the HIV infected women (Hussein and Galloway, 1985;Smart et al, 1987;Gordon and Duncan, 1991;Joshi et al, 2013;Campbell et al, 2016;Naud et al, 2016). However, several meta-analysis and systematic reviews of such studies underscored the paucity of information related to the adverse events during and after the procedure (Dolman et al, 2014;Cremer et al, 2018;Randall et al, 2019). Concerns have been expressed by some authors regarding the possibility of the women feeling more pain during TA (Maza et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…39,45,46 Thermal ablation has now been widely adopted within Malawi both within government and non-governmental organization (NGO)-supported screening services and its use is reported in other contexts. 49,47,48 Critically, in 2019, the WHO 43 issued revised guidance for treatment of cervical precancer lesions, for the first time supporting the use of thermal ablation. This guidance recognized the challenges relating to the cost and availability of a refrigerant gas for cryotherapy (as mentioned above), and the need for an evidence-based recommendation for use of thermal ablation in LICs.…”
Section: Thermal Ablationmentioning
confidence: 99%
“…Machines – both the traditional (WISAP) and newer hand-held models – are lightweight compared to cryotherapy equipment, and the hand-held models are also battery-operated or solar-powered (a WISAP C3 thermo-coagulator (https://www.wisap.de/Gynecology.html) and Liger thermo-coagulator (http://www.curemedicalglobal.com/)), respectively. Treatment time is short – WHO guidance recommends thermal ablation be provided at a minimum of 100°C for 20–30 s. 49 There is an initial cost outlay for the machine and probes, but ongoing maintenance costs are low. 11,34 In our experience in Malawi, cost savings compared with cryotherapy were realized after 50 treatments.…”
Section: Treatment Of Early Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies, thermal ablation did not cause any significant side effects, and the most common side effects were abnormal vaginal discharge and light vaginal bleeding. 20,[30][31][32] These reported side effects are comparable and less common than those reported for cryotherapy, the most widely used ablative therapy for CIN in sub-Saharan Africa. 33 False VIA-positive results were high among our study population; 20 (69%) of 29 VIA-positive women with histologic results did not have CIN.…”
Section: Discussionmentioning
confidence: 72%